Upaya Kolaborasi Pemerintah dan Masyarakat Dalam Mengatasi Pencemaran Lingkungan ditinjau dari UU PPLH - Hanifati Husna; Rafly Hakim; Ubaidillah Kamal (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Environmental pollution is a global issue that affects various aspects of life, including human health, ecosystem sustainability, and economic stability. This study examines collaborative efforts involving the active role of the government in implementing regulations, oversight, and law enforcement related to environmental protection, as well as the participation of the community in advocacy efforts and environmental actions. This research employs a normative juridical approach. In conducting the study, an analysis of literature references and secondary materials was performed. The results of this research indicate that the community has been given space by the government to collaborate in addressing environmental pollution based on the Environmental Protection Law. Stringent environmental laws against violations can minimize environmental damage. Preventive and repressive efforts have become part of environmental law enforcement, including administrative, criminal, and civil sanctions.